Preservation of Vestibular Function and Residual Hearing After Round Window Cochlear Implantation. Issue 7 (August 2019) - Stuermer, Konrad Johannes; Kluenter, Heinz Dieter; Lang-Roth, Ruth; Schwarz, David; Hüttenbrink, Karl-Bernd; Anagiotos, Andreas
Abstract : Objective: To examine the possible correlation between the loss of short-term residual hearing and vestibular function after cochlear implantation (CI). Study Design: Retrospective patient review. Setting: Academic tertiary referral center. Patients: One hundred twenty patients with normal vestibular function (VF) in the caloric testing and residual hearing (RH) at the frequencies 250, 500, and 1000 Hz on the surgery side between 2008 and 2016 were included in the study. Intervention: Primary CI on the first side via round window with a conventional full-length electrode. Main Outcome Measures: Changes of RH and VF 7 weeks after surgery were analyzed. Preservation of RH was defined as measurable postoperative thresholds at the frequencies 250, 500, and 1000 Hz in the pure-tone audiogram. Preservation of the VF after CI was assessed both by an absolute and relative threshold in the caloric testing. Results: Seven weeks after implantation, the preservation of RH was achieved in 52 (43.3 %) patients and the preservation of VF in 95 (79.2 %) patients on the operated side. There was no significant statistical correlation between these two parameters. Conclusion: The loss of RH was more than twice as frequent as the loss of VF. However, no statistical correlation between the failure of the two inner ear functions was found. The exact causes are still unknown, but our data could give an indication that there may be different underlying pathomechanisms.